Pengalaman Kehilangan dan Berduka pada Ibu yang Mengalami Kematian Bayi di Depok - Zakiyah Mujahidah; Achir Yani S. Hamid; Yossie Susanti E.P. (Universitas Muhammadiyah Semarang, 2015)
The purpose of this research study was to explore the experience of lost and grieving among women who experienced infant deaths. This research used a qualitative research method with phenomenological design to ten participants consisted of mothers in subdistrict Limo Depok city meeting the criteria. The result of this study revealed seven themes: the causes of infant deaths, the phase of grieving, responses after loss, social systems support, the lessons of lost, after loss expectations and coping strategies. It’s recommended that the units should be actively involved in facilitating and providing nursing care to the mothers to enable the mothers to cope with the feeling of lost and continues with their happy life.